Increasing Community College Completion Rates Among Low‐Income Students: Evidence from a Randomized Controlled Trial Evaluation of a Case‐Management Intervention. (5th September 2020) - Evans, William N.; Kearney, Melissa S.; Perry, Brendan; Sullivan, James X.
Abstract: Community college completion rates are low, especially among low‐income students. The existing policy and research attention has primarily focused on academic and financial challenges, but there is ample reason to think that non‐academic obstacles might be key drivers of dropout rates for low‐income students. This study focuses on the role of "life barriers" and investigates the effectiveness of intensive case‐management services for low‐income community college students. We evaluate the impact of the Stay the Course (STC) intensive case‐management program through a multi‐armed randomized controlled trial evaluation conducted between 2013 and 2016 in Fort Worth, Texas. Analysis of administrative records indicates that STC significantly increased persistence and degree completion for women; estimates for the full sample are imprecise. The statistically significant estimates for women imply that STC tripled associate's degree receipt by 31.5 percentage points. We find no difference in outcomes between students in an emergency financial assistance (EFA) only treatment arm and the control group. Given program costs of 4, 343 per person, the implied cost per additional associate's degree is 27, 140. This study complements existing literature on financial and informational interventions designed to increase completion rates and is most closely related to the smaller literature examining coaching and mentoring interventions.